Intermixing reactions in electrodeposited Cu/Sn and Cu/Ni/Sn multilayer interconnects during room temperature and high temperature aging - Chia, P.Y.; Haseeb, A.S. Md. Abdul (Springer, 2015)
Current push for miniaturization and 3D packaging makes it important to understand reactions in interconnects with ultra small volume. In order to reduce processing time and to have more homogeneous interconnects, solder can be designed in a multilayer form with components layer thickness in the sub-micron or even nanometer range. In this work, reaction kinetics in multilayer interconnects consisting stacks of Cu/Sn/Cu and Cu/Ni/Sn/Ni/Sn deposited by electrodeposition were investigated at room temperature and 150 A degrees C. The progress of the reaction in the multilayers was monitored by using XRD, SEM and EDX. Results show that by inserting a 70 nm thick nickel layer between copper and tin, premature reaction between Cu and Sn at room temperature can be avoided. The addition of the nickel layers also allows the selective formation of Cu6Sn5 which is considered to have better properties compared to Cu3Sn. Details of the reaction sequence and mechanisms are discussed.